Re-reading the Position of Women in Islamic-Iranian Mystical Texts (With Reference to Attar and Rumi’s Works) - Najmeddin Jabbari (Critical Literary Studies)
Contrary to the traditional disciple-making efforts presented by commentators of mystical works, which aim to consolidate a fanatical attitude towards mysticism and hide any epistemological defects, these works have their own disadvantages, similar to any other knowledge system. One of these disadvantages is the categorization of "women," which, due to the continuation of the patriarchal worldview and the Mithraic origin of Iranian-Islamic mysticism, has been approached with a dogmatic and gender-oriented perspective. Therefore, within the mystical tradition, despite occasional praises given to women in Sufi works, they are generally regarded as symbols of evil passion, and the love for them is seen as figurative and lustful. In these instances, the mystical texts acknowledge their own stance, and, often in contrast to the efforts of their fanatical admirers, provide an opportunity for so-called "destructive" analyses. The present article examines the contradictions within the works of two renowned mystical poets, Attar and Rumi, specifically regarding their portrayal of "woman". By adopting a deconstructive approach, often utilizing textual evidence, it aims to highlight their patriarchal attitude. Consequently, it concludes that while researchers of mystical works have often attempted to absolve the mystic poets of their patriarchal or misogynistic gender-oriented views, the mystics themselves have not done so.